THE EFFICACY AND SAFETY OF THE NEW DRUG APREMILAST FOR THE TREATMENT OF PSORIASIS AND PSORIATIC ARTHRITIS - Yu. L. Korsakova; L. N. Denisov (Научно-практическая ревматология)
Apremilast (AP) is a new phosphodiesterase  4 inhibitor for the treatment of psoriasis and psoriatic arthritis (PsA). Treatment  with AP reduces the level of proinflammatory cytokines and the activity of inflammatory changes.The positive impact of AP treatment on the course of psoriasis has been proven in a number of clinical trials, for example ESTEEM  1 (Efficacy and Safety Trial Evaluating the Effects of apreMilast in psoriasis), in which the treatment with AP has led to a decrease in PASI scores in patients with moderate and severe psoriasis en plaque: after 16 weeks, a 75% PASI improvement  was significantly more common  in patients taking AP 30 mg twice daily (33%) than in those who used placebo (PL) (5%) (p = 0.0001). In the PALACE 1 trial, the PsA patients were given AP at a dose of 20 or 10 mg twice daily. At 16 weeks, the patients who used AP at doses 20 and 30 mg twice daily, more frequently showed a 20% improvement  according to the American College of Rheumatology (ACR) response criteria (ACR20) than those who received PL (in 30.4, 38.1, and 19% of cases; p = 0.0166 and p = 0.0001, respectively). Following 52 weeks of AP treatment, ACR20 was achieved by 63.0% of the patients who took the drug at 20 mg twice daily, and by 54.6% of those who used 30 mg twice daily. The PALACE 1, PALACE 2, and PALACE 3 trials demonstrated that the most common  adverse events (AE) were diarrhea,  nausea, headache,  upper respiratory tract infections, and nasopharyngitis. Most AE were mild and moderate;  and the rate of therapy discontinuation due to AE was low.These PALACE trials covering 1493 patients have provided evidence for the efficacy and safety of AP in treating moderate PsA activity.